1981
DOI: 10.1113/jphysiol.1981.sp013958
|View full text |Cite
|
Sign up to set email alerts
|

Glycine transport in human erythrocytes.

Abstract: SUMMARY1. Glycine transport in human erythrocytes was resolved into five separate components of uptake. The first and major component of uptake was transport by a high-affinity (apparent Km 25/tM) Na+-and Cl--dependent system. This system was specific for glycine, sarcosine and proline; Br-but not I-was able to substitute for Cl-. Uptake by this route was inhibited < 20 % by the loop diuretics, bumetanide and furosemide (10-4M), suggesting that it was distinct from the Cl--dependent system responsible for Na+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 21 publications
3
56
0
Order By: Relevance
“…In addition we found that niflumic acid, a high-affinity inhibitor of anion exchange in red cells (Cousin & Motais, 1979), attenuated the volume-activated efflux of taurine. Although a small portion of taurine exists as an anion at physiological pH and glycine has been shown to be a substrate of the human red cell anion-exchange system (Ellory, Jones & Young, 1981) there are several lines of evidence to suggest that the DIDS-sensitive component of taurine (and glycine) efflux from mammary tissue is not mediated via an exchange system. First, the magnitude of the volume-sensitive taurine efflux was not increased by the presence of taurine in the incubation medium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition we found that niflumic acid, a high-affinity inhibitor of anion exchange in red cells (Cousin & Motais, 1979), attenuated the volume-activated efflux of taurine. Although a small portion of taurine exists as an anion at physiological pH and glycine has been shown to be a substrate of the human red cell anion-exchange system (Ellory, Jones & Young, 1981) there are several lines of evidence to suggest that the DIDS-sensitive component of taurine (and glycine) efflux from mammary tissue is not mediated via an exchange system. First, the magnitude of the volume-sensitive taurine efflux was not increased by the presence of taurine in the incubation medium.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that amino acids can utilize the anion exchanger is not new; Ellory et al (1981) found that glycine, under isosmotic conditions, is a substrate of the erythrocyte anion exchanger. However, the observation that the transport of sulfate, a substrate of the anion exchanger in mammary tissue (Shennan, 1989), is unaffected by cell swelling suggests that volume-activated amino acid efflux from rat mammary tissue does not use the anionexchange mechanism (Shennan et al 1994~2).…”
Section: Volume-activated Amino Acid Transportmentioning
confidence: 99%
“…The anion-transport system can bring about the net movement of anions, but it has been suggested that this occurs by 'tunneling' of the anion, rather than exchange of the anion with an unloaded site (Knauf, Law & Marchant, 1983;Frdhlich, 1984). Glycine can be carried by the red cell anion system (Ellory, Jones & Young, 1981). It is not known if the transported species is the zwitterion, or one of the charged forms.…”
Section: Mechanism Of Pb Transportmentioning
confidence: 99%